Luminescence properties of Eu 2+ and Mn 2+ doped Sr 1.7Mg 0.3SiO 4 phosphors - Guo, M.; Huang, L.; Zhao, S.; Deng, D.; Wang, H.; Hua, Y.; Jia, Guohua; Xu, S. (Elsevier Science Ltd, 2012)
Eu 2+, Mn 2+ doped Sr 1.7Mg 0.3SiO 4 phosphors were prepared by high temperature solid-state reaction method. Their luminescence properties were studied. The emission spectra of Eu 2+ singly doped Sr 1.7Mg 0.3SiO 4 consist of a blue band (455 nm) and a green band (550 nm). The relative intensities of two emissions varied with Eu 2+ concentration. Eu 2+ and Mn 2+ co-doped Sr 1.7Mg 0.3SiO 4 phosphors emit three color lights and present whitish color. The blue (455 nm) and green (550 nm) emissions are attributed to the transitions of Eu 2+, while the red (670 nm) emission is originated from the transition of Mn 2+ ion. The results indicate the energy transfer from Eu 2+ to Mn 2+. The mechanism of the energy transfer is resonance-type energy transfer due to the spectral overlap between the emission of Eu 2+and the absorption of Mn 2+. © 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.